Eplerenone for early cardiomyopathy in Duchenne muscular dystrophy: a randomised, double-blind, placebo-controlled trial. Issue 2 (February 2015) - Raman, Subha V; Hor, Kan N; Mazur, Wojciech; Halnon, Nancy J; Kissel, John T; He, Xin; Tran, Tam; Smart, Suzanne; McCarthy, Beth; Taylor, Michael D; Jefferies, John L; Rafael-Fortney, Jill A; et al.
Summary Background Cardiomyopathy is a leading cause of death in patients with Duchenne muscular dystrophy and myocardial damage precedes decline in left ventricular systolic function. We tested the efficacy of eplerenone on top of background therapy in patients with Duchenne muscular dystrophy with early myocardial disease. Methods In this randomised, double-blind, placebo-controlled trial, boys from three centres in the USA aged 7 years or older with Duchenne muscular dystrophy, myocardial damage by late gadolinium enhancement cardiac MRI and preserved ejection fraction received either eplerenone 25 mg or placebo orally, every other day for the first month and once daily thereafter, in addition to background clinician-directed therapy with either angiotensin-converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB). Computer-generated randomisation was done centrally using block sizes of four and six, and only the study statistician and the investigational pharmacy had the preset randomisation assignments. The primary outcome was change in left ventricular circumferential strain (Ecc) at 12 months, a measure of contractile dysfunction. Safety was established through serial serum potassium levels and measurement of cystatin C, a non-creatinine measure of kidney function. This trial is registered with ClinicalTrials.gov, number NCT01521546. Findings Between Jan 26, 2012, and July 3, 2013, 188 boys were screened and 42 were enrolled. 20 were randomly assigned to receive eplerenone and 22 to receive placebo, of whom 20 in the eplerenone group and 20 in the placebo group completed baseline, 6-month, and 12-month visits. After 12 months, decline in left ventricular circumferential strain was less in those who received eplerenone than in those who received placebo (median ΔEcc 1·0 [IQR 0·3–2·2] vs 2·2 [1·3–3·1]; p=0·020). Cystatin C concentrations remained normal in both groups, and all non-haemolysed blood samples showed normal potassium concentrations. One 23-year-old patient in the placebo group died of fat embolism, and another patient in the placebo group withdrew from the trial to address long-standing digestive issues. All other adverse events were mild: short-lived headaches coincident with seasonal allergies occurred in one patient given eplerenone, flushing occurred in one patient given placebo, and anxiety occurred in another patient given placebo. Interpretation In boys with Duchenne muscular dystrophy and preserved ejection fraction, addition of eplerenone to background ACEI or ARB therapy attenuates the progressive decline in left ventricular systolic function. Early use of available drugs warrants consideration in this population at high risk of cardiac death, but further studies are needed to determine the effect of combination cardioprotective therapy on event-free survival in Duchenne muscular dystrophy. Funding BallouSkies, Parent Project for Muscular Dystrophy, US National Center for Advancing Translational Sciences, and US National Institutes of Health.